FENOMENA-FENOMENA DI SEPUTAR KEBIJAKAN INITIAL PUBLIC OFFERING (IPO) DAN PENGUKURAN KINERJA PERUSAHAAN DI INDONESIA - Sucipto, Agus (IQTISHODUNA, 2008)
Usually, the firm will go public start it by initial public offering (IPO) at primary market. So, it is sold  at secondary market. Something is no needed by emitent, that is occurred too high underpricing, that is situation where share price at the first day at secondary market higher than primary market. Underpricing is interesting phenomenon, because a large part of  market security in the world is experience. Other phenomenon accompany IPO is asymmetric information. Although investors have enough information about the IPO’s firm,  asymmetric information remains will be happened. This situation motivate management  to manipulate his performance both  before and the moment of IPO. This manipulation is known earnings management that resulted underperformance after IPO. Nevertheless, the other side,  earnings management will  influence  value of the firm.This condition is happened cause of earnings is published at the moment of IPO relatively better so market’s response is good. The policy of earnings management is addressed to give positive signal to market about the firm. It appear at the statement of performance (usually at the IPO’s prospectus). However, at the long time, this positive signal can’t be  maintained by management, it is reflected at decreasing performace published by the firm.